Family Strategies to Support Siblings of Pediatric Hematopoietic Stem Cell Transplant Patients - White, Taylor E. (Pediatrics, 2017)
OBJECTIVE: To describe the strategies families report using to address the needs and concerns of siblings of children, adolescents, and young adults undergoing hematopoietic stem cell transplant (HSCT). METHODS: A secondary semantic analysis was conducted of 86 qualitative interviews with family members of children, adolescents, and young adults undergoing HSCT at 4 HSCT centers and supplemented with a primary analysis of 38 additional targeted qualitative interviews (23 family members, 15 health care professionals) conducted at the primary center. Analyses focused on sibling issues and the strategies families use to address these issues. RESULTS: The sibling issues identified included: (1) feeling negative effects of separation from the patient and caregiver(s); (2) experiencing difficult emotions; (3) being faced with additional responsibilities or burdens; (4) lacking information; and (5) feeling excluded. Families and health care providers reported the following strategies to support siblings: (1) sharing information; (2) using social support and help offered by family or friends; (3) taking siblings to the hospital; (4) communicating virtually; (5) providing special events or gifts or quality time for siblings; (6) offering siblings a defined role to help the family during the transplant process; (7) switching between parents at the hospital; (8) keeping the sibling’s life constant; and, (9) arranging sibling meetings with a certified child life specialist or school counselor. CONCLUSIONS: Understanding the above strategies and sharing them with other families in similar situations can begin to address sibling issues during HSCT and can improve hospital-based, family-centered care efforts.